An acoustic array imaging algorithm for 3D display based on MIMO and MUSIC location fusion - Wei Yong; Zhao Ping; Li Lifang; Wu Linjing; Ji Qianqian; Wang Wei (2010 International Conference on Computer Application and System Modeling (ICCASM 2010), 2010)
In this paper, an acoustic imaging algorithm based on acoustic array Multiple-Input Multiple-Output (MIMO) and Multiple Signal Classification (MUSIC) by location algorithm fusion is proposed to realize Three Dimension (3D) location estimation and display for future mobile system. By combined with MIMO beam estimation and MUSIC estimation algorithm, the location fusion algorithm with 3D display advantage can be achieved, because the MIMO data pretreating and data fusion are used to increase location imaging precision and resolution, so that a robust and anti-interference location display algorithm can be obtained. We carried out Modeling and Simulation for MIMO beam location algorithm, MUSIC estimation algorithm and location fusion algorithm, and made a compare and analysis on simulation results. Simulation results show that the location fusion algorithm is provided with reliable feasibility, improved precision and resolution for 3D imaging display.